2020
DOI: 10.1038/s41598-019-57286-x
|View full text |Cite
|
Sign up to set email alerts
|

Polycystin 2 is increased in disease to protect against stress-induced cell death

Abstract: Polycystin 2 (PC2 or TRPP1, formerly TRPP2) is a calcium-permeant Transient Receptor Potential (TRP) cation channel expressed primarily on the endoplasmic reticulum (ER) membrane and primary cilia of all cell and tissue types. Despite its ubiquitous expression throughout the body, studies of PC2 have focused primarily on its role in the kidney, as mutations in PC2 lead to the development of autosomal dominant polycystic kidney disease (ADPKD), a debilitating condition for which there is no cure. However, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 109 publications
0
17
0
Order By: Relevance
“…We assume that excess PC2 under WT conditions is physiologic while the biological significance of further PC2 upregulation may be context dependent. Brill et al demonstrated that Pkd2 depleted LLC‐PK1 cells are more prone to cell death in response to serum starvation or tunicamycin, leading these authors to conclude that upregulation of PC2 is a protective stress response 42 . In contrast transgenic overexpression of PC2 in mice can result in cyst formation depending on the dosage 12,43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that excess PC2 under WT conditions is physiologic while the biological significance of further PC2 upregulation may be context dependent. Brill et al demonstrated that Pkd2 depleted LLC‐PK1 cells are more prone to cell death in response to serum starvation or tunicamycin, leading these authors to conclude that upregulation of PC2 is a protective stress response 42 . In contrast transgenic overexpression of PC2 in mice can result in cyst formation depending on the dosage 12,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Brill et al demonstrated that Pkd2 depleted LLC-PK1 cells are more prone to cell death in response to serum starvation or tunicamycin, leading these authors to conclude that upregulation of PC2 is a protective stress response. 42 In contrast transgenic overexpression of PC2 in mice can result in cyst formation depending on the dosage. 12,43 Whether extra PC2 in the in vivo Pkd1 null state is protective, detrimental or has a neutral effect remains to be resolved.…”
Section: (B)mentioning
confidence: 99%
“…It is unclear whether TRPP downregulation in MS lesions is beneficial or detrimental. On one hand, it may be detrimental because TRPP1 and TRPP3 channels are important for maintaining Ca 2+ homeostasis and contribute to cell proliferation (Xiao and Quarles, 2010 ; Xiao et al, 2010 ), while TRPP1 knockdown results in increased susceptibility to stress-induced cell death in kidney epithelial cells (Brill et al, 2020 ). On the other hand, overexpression of TRPP contributes to apoptosis (Xiao and Quarles, 2010 ; Xiao et al, 2010 ), and TRPP1 is upregulated as a direct consequence of ER and oxidative stress during pathological conditions.…”
Section: K + Channelsmentioning
confidence: 99%
“…genepharma.com 28 Primer of GAPDH Forward: 5 0 -AGGTCGGTGTGAACGGATTTG-3 0 Reverse: 5 0 -GGGGTCGTTGATGGCAACA-3 0 Genewiz, Suzhou, China; www.genewiz. com.cn 29 IL-33: interleukin-33; ST2 suppressor of tumorigenicity 2; WT: wild type; MT: mutant type in which the interaction sites with miR547-5p were mutated; NC: nonspecific negative control sequence; rno-miR547-5p: rat noncoding miRNA-547-5p; Sh-IL-33: lentivirus particles conjugated with short hairpin RNA which inhibits the expression of IL-33 protein. Bolded and underlined nucleotides in the wild type of IL-33 or ST2 indicate (also see Figure 1(a)) the interaction sites with miR547-5p predicted with TargetScan (http://www.targetscan.org/).…”
Section: Western Blot Analysismentioning
confidence: 99%